The struggle over Lao PDR’s forests: New opportunities for improved forest governance? - Sebastian Koch (Pacific Geographies, 2017)
The forests of Lao PDR have dramatically diminished in recent decades. The main drivers of deforestation are changes in land use with forests being converted to agriculture, hydropower, mining and plantations. The main drivers of degradation are legal and illegal logging, especially salvage logging and pioneering shifting cultivation. Underlying drivers are poverty, weak governance and corruption, poor law enforcement and limited capacities as well as unclear, often contradictory legislation and the international demand for timber, rubber, food, electricity and minerals. The situation regarding forest governance, however, seems to slightly improve starting in early 2016. After years of little or no progress in terms of REDD+ the country prepared a proposal to receive performance-based payments which has been accepted into the FCPF Carbon Fund. Lao PDR also entered into the EU-FLEGT negotiations. A new government, which has been in office since early 2016, is increasingly trying to combat illegal logging and timber exports.